Tumor-infiltrating immune cell status predicts successful response to immune checkpoint inhibitors in renal cell carcinoma - Akira Kazama; Vladimir Bilim; Masayuki Tasaki; Tsutomu Anraku; Hiroo Kuroki; Yuko Shirono; Masaki Murata; Kaede Hiruma; Yoshihiko Tomita (Scientific Reports, 2022)
Abstract Immune checkpoint inhibitors (ICI) have dramatically changed the treatment of metastatic renal cell carcinoma (mRCC). Although many studies have reported biomarkers as predicting the efficacy of ICI in mRCC, they remain controversial and have challenges to apply in real-world practice. We evaluated prognostic significance of multiple molecules associated with tumor immunity in patients treated with ICI. The molecules were detected in tumor tissues by immunohistochemical staining. We identified CD8-positive T cells and CD68-positive macrophages infiltrating into the tumor tissue as significant favorable prognostic factors for ICI treatment. Conversely, high expression of CD4-positive T cells was associated with poor response to ICI. Furthermore, we demonstrated that scoring for the expression status of these three molecules provides a remarkably accurate biomarker in patients with mRCC. Even the classical approach of immunohistochemistry could predict the outcome of ICI treatment by assessing the combined status of tumor-infiltrating immune cells.